InterPACIFIC project: Comparison of invasive and non-invasive methods for seismic site characterization. Part II: Inter-comparison between surface-wave and borehole methods. Issue 82 (March 2016) - Garofalo, F.; Foti, S.; Hollender, F.; Bard, P.Y.; Cornou, C.; Cox, B.R.; Dechamp, A.; Ohrnberger, M.; Perron, V.; Sicilia, D.; Teague, D.; Vergniault, C.
Abstract: The InterPACIFIC project was aimed at assessing the reliability, resolution, and variability of geophysical methods in estimating the shear-wave velocity profile for seismic ground response analyses. Three different subsoil conditions, which can be broadly defined as soft-soil, stiff-soil, and hard-rock, were investigated. At each site, several participants performed and interpreted invasive measurements of shear wave velocity ( Vs ) and compression wave velocity ( Vp ) in the same boreholes. Additionally, participants in the project analysed a common surface-wave dataset using their preferred strategies for processing and inversion to obtain Vs profiles. The most significant difference between the invasive borehole methods and non-invasive surface wave methods is related to resolution of thin layers and abrupt contrasts, which is inherently better for invasive methods. However, similar variability is observed in the estimated invasive and non-invasive Vs profiles, underscoring the need to account for such uncertainty in site response studies. V S, 30 estimates are comparable between invasive and non-invasive methods, confirming that the higher resolution provided by invasive methods is quite irrelevant for computing this parameter. Highlights: Reliability of Vs models from geophysical tests is studied with a blind test. Three subsoil conditions are considered: soft soil, stiff soil, rock outcrop. In-hole methods and surface wave methods are considered. In-hole methods provide high resolution and accuracy, but the precision is similar. There is a good match between estimates of V S, 30, with comparable variability.